Can an economic-based approach support the development of Antarctica´s regulatory framework for bioprospecting? - Asma Ebrahim 1973- (2024)
This thesis examines the regulatory framework for the Bioprospecting of Antarctic Krill, incorporating both the Convention on Biodiversity (CBD) and the agreement on Biodiversity Beyond National Jurisdiction (BBNJ) adopted in 2023 into the Antarctic context alongside the Antarctic instruments and most obviously the Convention for the Conservation on Marine living Resources (CCAMLR). This is an unorthodox and unconventional study developing a hypothesis that integrates international law with economic and commercial principles to create a foundational pathway to facilitate CCAMLR’s objectives of conservation and rational use of Antarctic marine living resources. The study outlines the ecological significance of Antarctic Krill, Euphausia superba, a keystone species in the Southern Ocean, that is increasingly targeted for its commercial value, necessitating a nuanced approach for the conservation and sustainable use thereof. The rapidly emerging interest in its bioprospecting argues the need for a regulatory approach that balances economic pursuits with ecological sustainability. A critical qualitative and quantitative analysis of bioprospecting activities is made using the Economics of Law and economic-based tools, principles and practices. This provides insights, designing activities based on their commercial nature, may achieve effective compliance and monitoring relative to applicable governing regulatory instruments. The Bioprospecting concept is assessed through multidimensional economic perspectives in the value chain of Bioprospecting activities. It examines the establishment of bioprospecting frameworks, as per the CBD directives, in two sovereign states of differing political developmental stages, that exemplifies two methodologies that may applied in Antarctica despite its absence of recognized territorial sovereignty. The research delves into the complexities of harmonizing the Antarctic Treaty System’s (ATS) institutional architecture and the newly adopted International Legal Instruments to resolve the ...